High-Resolution Molecular Imaging Via Intravital Microscopy: Illuminating Vascular Biology In Vivo - Taqueti, Viviany R. (2013)
Complications of atherosclerosis and thrombosis are leading causes of death worldwide. While experimental investigations have yielded valuable insights into key molecular and cellular phenomena in these diseases of medium- and large-sized vessels, direct visualization of relevant in vivo biological processes has been limited. However, recent developments in molecular imaging technology, specifically fluorescence imaging agents coupled with high-resolution, high-speed intravital microscopy (IVM), are now enabling dynamic and longitudinal investigations into the mechanisms and progression of many vascular diseases. Here we review recent advances in IVM that have provided new in vivo biological insights into atherosclerosis and thrombosis.